Restorative Justice Principles and Practices and the Discourse of Respect: A Case Study of a Teacher in a Custodial Establishment for Young Offenders - Bocale, Paola (Mediterranean Journal of Social Sciences, 2020)
This study aims to explore discourses of respect in the Education Department of a Young Offenders Institution (HMYOI X). The research builds upon the existing literature on the concept of respect both in restorative justice and in prisons to develop a deeper understanding of perspectives on respect in custodial education. More specifically, the study examines a self-narrative elicited from a teacher working in a YOI in England to investigate the discourses of respect which prevail in a custodial institution. The research findings provide a better understanding of the discourses and dynamics of respect within an educational custodial setting and of some of the problems and challenges that need to be addressed in enhancing and assessing the use of restorative justice in prisons.